Brewster site zooarchaeology reinterpreted: understanding levels of animal exploitation and bone fat production at the Initial Middle Missouri type site. Issue 1 (31st March 2015) - Karr, Landon P.
Abstract : Zooarchaeological analyses of Middle Missouri Plains village sites have traditionally relied on species lists and counts of individuals and specimens as a means of interpreting the prehistoric past. The published literature from some of these sites suggests that the fractured and fragmented nature of large mammal bones at Middle Missouri sites serves as evidence of bone marrow and bone grease exploitation. Quantitative approaches to identifying bone fat exploitation and characterising bone fracture patterns allow for more nuanced interpretations of the complex Middle Missouri period village sites of South Dakota and Northwest Iowa. The application of new methods to study the archaeofauna of the Brewster site allows for a reinterpretation of the site's animal economies. New data reveal a consistent pattern of bone fat exploitation at the Brewster site over time, suggest that bone fat exploitation was practiced as an occasional or small-scale activity at the site, and demonstrate the potential of these methods as a means of reinterpreting complex zooarchaeological assemblages. This study also discusses some of the methodological and sampling issues that are critical to achieving accurate, evidence-based results when assessing complex zooarchaeological deposits. Statement of significance The Brewster site is a Native American village in Northwest Iowa that was likely occupied between AD 1100 and AD 1200. The villagers at the Brewster site hunted large mammals from the landscape surrounding their village, and practiced some of the earliest agriculture in the region. As a result, large numbers of bison bones are preserved archaeologically at the site. ~140 kg of bone, excavated in 1970, has been analyzed and reported in this article. When fractured and fragmented bones are found in the archaeological record, they are often associated with the exploitation of bone marrow and bone grease, two highly nutritious substances. This article reports on the relative importance of the bones and bone fragments at the Brewster site with regard to their use and utility as sources of bone fats. While there is some evidence to suggest that the bones were intentionally fractured and fragmented, the evidence suggests that the Brewster villagers frequently ignored the dietary potential of bone fats. Data availability The authors confirm that all data underlying the findings are fully available without restriction. All relevant data are contained within the paper.